2014
DOI: 10.1515/gps-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of waste cooking oil transformation by transesterification and esterification reactions in oscillatory baffled and microstructured reactors for biodiesel production

Abstract: The transformation of waste cooking oils for fatty acid methyl ester production is investigated in two intensified technologies: microstructured Corning ® and oscillatory baffled NiTech ® reactors, compared to a reference batch reactor to quantify the process intensification provided by each technology. Both reactors achieve high conversions in shorter times. For transesterification, 96 wt.% of esters are obtained in 1.4 min at 97°C in the Corning ® reactor and 92.1 wt.% of esters in 6 min at 44°C in the NiTec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In each experimental run, the WCO oil and the methoxide (solution of KOH and methanol) were poured inside the OBR with a methanol to oil molar ratio of 6:1 and a catalyst concentration of 1%, which have shown to provide the best reaction conversion in a number of studies [7,29,30,33]. The reactor temperature (40°C, 50°C and 60°C) was stabilized before the oscillation generation mechanism started.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each experimental run, the WCO oil and the methoxide (solution of KOH and methanol) were poured inside the OBR with a methanol to oil molar ratio of 6:1 and a catalyst concentration of 1%, which have shown to provide the best reaction conversion in a number of studies [7,29,30,33]. The reactor temperature (40°C, 50°C and 60°C) was stabilized before the oscillation generation mechanism started.…”
Section: Methodsmentioning
confidence: 99%
“…At 50°C and after a residence time of 10 min, the authors obtained methyl ester yields in the range of 78-85% depending on the methanol-to-oil ratio. Mazubert et al [29] studied the process intensification of biodiesel production from waste cooking oil in a continuous glass OBR for relatively low temperatures and a few different oscillation conditions. At low temperature (27°C), the Re o in the range of 28-42 does not have a significant effect on reaction yield, which is between 82.3 wt% and 87.3 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may not necessarily be the best operating range for processes, e.g. Mazubert et al (2014) observed a decrease in the conversion of waste cooking oil into methyl esters for ;< > 0.1. The velocity ratio, ψ, describes the relationship between the oscillatory and net flow.…”
Section: Introductionmentioning
confidence: 99%
“…UCO as a feedstock for HDRD application has been adopted in recent times. The cheapest source of feedstock for the production of HDRD is UCO [30]. Rocha Filho et al reported that more than 200 000 tons of used cooking oil is generated in South Africa per/annum [31,32].…”
Section: Feedstock Optionsmentioning
confidence: 99%